Meningkatan Hasil Belajar Matematika Pada Peserta didik Kelas XI Melalui Model Pembelajaran Drill - Agnes Djunijati (JURNAL INOVASI PENDIDIKAN DAN SAINS, 2023)
This study aims to determine the application of the Drill learning model is able to improve Mathematics learning outcomes for students of grade XI KPR 1 SMK Negeri 1 Banyudono semester gasal academic year 2022/2023. This research was conducted at SMK Negeri 1 Banyudono for six months. The subjects of this study were 3.6 students of class XI KPR 1 SMK Negeri 1 Banyudono . This study was designed for classroom action research. Research is conducted in two cycles and each cycle consists of four stages, namely action planning, action implementation, observation and evaluation, and analysis and reflection. Each cycle is carried out with three meetings and each meeting is 2 x 45 minutes. The data collection techniques used are observation, test and documentation techniques. The data analysis technique used is comparative descriptive. This research was carried out in collaborationwith researchers, students, and teachers who teach other mathematics subjects. Based on the results of the study, it can be concluded that the application of the Drill learning model is able toimprove thematic learning outcomes for students of grade XI KPR 1 SMK Negeri 1 Banyudono in the first semester of the academic year 20, 22/20, 23. From the data on the implementation of research that has been carried out, the results of increasing student mathematics learning achievement from 18 students (5 0%) who were completed in the pre-cycle to 2.7 students (7.5%) who were completed in the first cycle and increased to 36 students (100 %) that reaches the limit of learning completeness. The average score of Mathematics learning achievement increased from 69.86 in the pre-cycle to 77.50 or an increase of 11% in the first cycle and to 87.78 or an increase of 2.6% in the second cycle.